Overview Of RAMS Analysis and ITS Implementation in Railway Vehicles - Muhamad Abdurrochman; Rachman Setiawan; Vani Virdyawan (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2024)
Reliability, availability, maintainability, and safety (RAMS) analysis, as a tool to ensure performance, safety, and cost-effectiveness throughout the system’s life cycle, has been widely applied in various industries, including the railway industry, specifically railway vehicles. This article provides an overview of various studies exploring the implementation of RAMS analysis in railway vehicles. This literature review consists of an introduction, method, RAMS analysis, results and discussion, and conclusion. Several studies on the implementation of RAMS analysis in railway vehicles are presented and explained, and key points from each study are discussed to provide a comprehensive overview of the implementation of RAMS analysis in railway vehicles. In general, the benefits of the implementation of RAMS analysis are enhanced performance (reliability, availability, and maintainability), safety, and cost-effectiveness of railway vehicles throughout their life cycle. However, many studies only focus on one or a few aspects of performance, safety, or cost-effectiveness without comprehensive discussions of all these aspects. Additionally, many studies only concentrate on the operational phase, including maintenance and repair, without a complete discussion of the entire life cycle from concept to disposal stage.